Students’ Perception on Intercultural Reading Material for English Learning - Faoyan Agus Furyanto; Iwansyah Putra; Neneng Islamiah (Universitas Pahlawan Tuanku Tambusai, 2021)
The adequacy of the intercultural-based English material depends on many factors, such as the students’ cultural background, the complexity of the problem situation provided in the material, the sensitivity of the material topic, and the students' experience to the topic discussion. Therefore, it was needed to get students’ response to the material given during the English learning. The objective of this study was to investigate students’ perceptions on intercultural reading material which were developed by the lecturers for English learning. The students’ perception was related to their motivation, difficulties, and the material efficacy. The study conducted a survey approach and involved 93 students. The participants were randomly selected from two study program in Surabaya Aviation Polytechnic. The data were collected through questionnaire. Further, the collected data was analyzed by performing the descriptive analysis (percentage and frequency) using SPSS version 22. The findings show that students have positive attitudes towards the material implemented in English learning